The Role Of Insurance In Risk Management For Small Businesses (Texas Journal of Multidisciplinary Studies, 2025)
Small businesses are increasingly recognized as vital contributors to economic growth, job creation, and innovation. However, due to their limited financial resources and operational capacities, they are particularly vulnerable to a wide range of risks, including property damage, liability claims, employee injuries, and business interruptions. Insurance plays a fundamental role in helping small enterprises manage these risks effectively, providing a critical safety net that enhances their resilience and long-term sustainability.